Pengelolaan Hiperkolesterolemia Lansia melalui Intervensi Nonfarmakologis Berbasis Komunitas - Silvia Rizki Nurcahyani; Nina Pamela Sari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Hypercholesterolemia is a major risk factor for cardiovascular disease in the elderly, where the aging process causes a decline in fat metabolism and an increased potential for cholesterol accumulation in the blood. To address this issue, this article aims to synthesize various community-based non-pharmacological interventions used to control cholesterol levels in the elderly in Indonesia. The method used is a descriptive systematic literature review based on the PRISMA 2017–2025 guidelines, by reviewing five articles that met the following criteria: elderly population, non-pharmacological intervention, community-based, and pre-post outcome data. The results of the synthesis indicate that interventions in the form of health education, cholesterol screening, and physical activity such as elderly exercise consistently increase knowledge, awareness, and reduce total cholesterol levels, as seen in studies by Harianja et al. (2020), Risnawati & Sari (2022), Astuti (2022), Athiutama et al. (2023), and Subagyo et al. (2025). Overall, a community approach combining health education and regular physical activity has been shown to be effective as a non-pharmacological strategy in controlling cholesterol in older adults, although most studies still use pre-experimental designs and community services, so further research with more robust methodology is needed.